The Relationship between Knowledge About Hypertension and Nutritional Status with Blood Pressure Control in Hypertension Sufferers at the Pasundan Community Health Center, Samarinda City - Nurhaliza; Joko Sapto Pramono; Kurniati Dwi Utami (PT FORMOSA CENDEKIA GLOBAL, 2023)
The number of hypertension sufferers continues to increase, with East Kalimantan ranking 3rd highest in Indonesia. Pasundan Community Health Center, Samarinda City ranks second in terms of prevalence. Hypertension is influenced by factors that can and cannot be changed, including knowledge and nutritional status. Knowledge and nutritional status can influence blood pressure and its control measures. The research aims to determine the relationship between knowledge about hypertension and nutritional status with blood pressure control at the Pasundan Community Health Center. The research was carried out in March-April 2023. There were 53 respondents. Data collection was carried out by anthropometric measurements and interviews to fill out the questionnaire. Data were analyzed using chi-square with α<0.05. The results of the study showed that the p-value was 0.000 (α<0.05), meaning that there was a relationship between knowledge about hypertension and nutritional status and blood pressure control.